Revised Bloom’s Taxonomy: A Review-Based Study - Devkota, Tika Ram; Tamrakar , Pratima; Devkota, Krishna Maya (ILAM इलम, 2026)
Revised Bloom’s taxonomy (RBT) is one of the popular learning outcome frameworks, instructional planning frameworks, and alignment structures of assessment in modern education. This study is carried out to review the literature related to the RBT that has developed over the years, its conceptual framework, application in pedagogical practices, advantages, limitations, and implications. It is based on the qualitative systematic review methodology, which included identification, screening, extraction, and synthesis of academic sources published in 2001-2024. The results show that the two-dimensional model of RBT, which includes the knowledge dimension and cognitive process dimension, offers an elaborate framework of curriculum and assessment design. The taxonomy enhances clarity in pedagogy, encourages thinking at a higher order, and is consistent with the requirements of the 21st century. Limitations assume a hierarchy may be biased to Western epistemology and inconsistent in their classroom applications because of the limited capacity of the teacher. It concludes that RBT is still a foundational framework that needs to be adapted to the context, teacher training, and combined with modern digital and competency- based education reforms.